Cajal, the neuronal theory and the idea of brain plasticity - Jairo A. Rozo; Jairo A. Rozo; Irene Martínez-Gallego; Antonio Rodríguez-Moreno (Frontiers Media S.A., 2024)
This paper reviews the importance of Cajal's neuronal theory (the Neuron Doctrine) and the origin and importance of the idea of brain plasticity that emerges from this theory. We first comment on the main Cajal's discoveries that gave rise and confirmed his Neuron Doctrine: the improvement of staining techniques, his approach to morphological laws, the concepts of dynamic polarisation, neurogenesis and neurotrophic theory, his first discoveries of the nerve cell as an independent cell, his research on degeneration and regeneration and his fight against reticularism. Second, we review Cajal's ideas on brain plasticity and the years in which they were published, to finally focus on the debate on the origin of the term plasticity and its conceptual meaning, and the originality of Cajal's proposal compared to those of other authors of the time.